A Comissão da Verdade no Brasil: a luta pela memória em uma democracia fragilizada - Celia Regina do Nascimento de Paula; Fernando Antonio da Costa Vieira (Revista Crítica de Ciências Sociais, 2020)
Brazil’s National Truth Commission (CNV), established in 2012, presented a report of its actions in 2014. By publishing the report, the CNV was able to identify the agents of the State who violated human rights by presenting reports on the deaths of 434 people, victims of arbitrary actions, including descriptions of torture techniques, executions, illegal arrests, disappearances and hiding victim’s bodies. The present work aims to discuss CNV action within the limits that have been imposed – those which heed the Amnesty Law of 1979 – and the axis of the struggle to rescue the missing memory denied to the political desaparecidos. The analysis of documents produced by the CNV, and the reports produced by the media, will be the material used for the production of this article.